Os fundamentos do agir moral em Kant - Fernando, Celestino Taperero (2018)
The purpose of this dissertation is to understand the moral value of human action in Kant's practical philosophy. Kant argues that morality is the principle of universal reason, capable of limiting human impulses, since, by virtue of natural needs. The moral conscience in this circumstance is a product of pure practical reason, which enables the application of theory to practice in function of the freedom of the transcendental subject to think and act. However, the categorical imperative is the command of moral actions, which is found in the autonomous subject, through the relation between goodwill and freedom. And dignity is a quality that naturally finite beings have as moral beings. The dignity of the human is translated in his capacity to act according to the representation of laws determined by himself, so that man should not be subject to any other purpose than that of his own reason, namely that of his own morality, which implies the fulfillment of "duty for duty. Faced with this idea, the human person is himself the measure and source of duty (Solen). Because reason knows only what it has projected itself. Whereas the pure "I" of the person is only possible when there is recognition that he is a being of duties, right and autonomous. Kantian formality starts with the distinction between morality and legality in order to allow coexistence between them. It is also in this position that the concept of law has its roots. For the author, the relationship between ethics and law is a relationship of subordination.